UNDERSTANDING THE INTERNATIONALISATION MOTIVATION AND FRANCHISING STRATEGY: A STUDY OF AN INDONESIAN STREET FOOD SME IN MALAYSIA - Fadhilla Khansa,; Ramona Blanes,; Zurina Mohaidin, (Journal of Islamic, Social, Economics and Development, 2022)
This paper is the findings from a study that explores the internationalisationmotivation and process, including models, the country selection and franchise strategy, as wellas the critical success factors of Indonesian street food SME in Malaysia. The emergence ofSMEs in developing countries is a contributing driver of economic development andemployment. Malaysia as a neighbouring country has a very similar character of society andculture becomes the first country for an Indonesian business that wants to expandinternationally. The purpose of this research is to provide a framework to create a clearunderstanding about the internationalisation motivation and franchising strategy of Indonesianstreet food SME in Malaysia. The data were collected from a single case study of Kebab TurkiBaba Rafi, an Indonesian street food SME that has successfully expanded internationally tonine countries with more than 1200 outlets. The result shows that market seeking is the mainmotivation for Kebab Turki Baba Rafi in internationalising to Malaysia. The company adoptsa network approach and chooses the franchise strategy as the entry mode strategy to Malaysiato minimise risks. The company has particular criteria in selecting the destination country forinternationalisation and its master franchisee.